Meningkatkan Kreativitas Anak Usia Dini Melalui Kegiatan Mewarnai dengan Mencampurkan Warna Dasar - Irmayanti, Delviera; Imaniar, Dewi Permata; Marwa, Alya Shofia; Febriani, Azhrin; Firmansyah, Andan (Yayasan Inspirasi El Burhani, 2024)
The development of creative potential peaks at an early age so that early childhood education plays an important role in developing children's creativity and skills, one of the educational game tools (APE) that can increase children's creativity is coloring.Objective: This community service is carried out with the aim of increasing creativity in early childhood through coloring activities and mixing basic colorsMethod: The method used is observational with an educational game tool (APE) coloring pictures with watercolors and creating new colors from mixing basic colors which was carried out on 12 respondents in Banjarharja Hamlet, Kertajaya Village, Lakbok District, Ciamis Regency.Results: Based on the Likert scale, timeliness came, duration and implementation pointed to a score of 20 out of 5 activity points, which means on time.Conclusion: The participants took part in the activities in an orderly, attractive and conducive manner, there was a change in the children after carrying out the core activities, namely the children looked happier and were able to know the new colors that were produced from the basic colors.